2020
DOI: 10.1007/s10508-020-01837-1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Inhibition and Sexual Excitation Scales in Men: Psychometric Properties of a Polish Adaptation

Abstract: The present study aimed to develop a Polish version of the Sexual Inhibition/Sexual Excitation Scale (SIS/SES-PL) and explore its psychometric validity in a sample of 498 men aged between 18 and 55 years. We used exploratory and confirmatory factor analyses to obtain the best model fit. Out of the 45 items in the original scale, 32 items with eight subscales and three higher-order factors: (sexual excitation [SES], sexual inhibition due to performance failure [SIS1], and sexual inhibition due to performance co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 48 publications
2
13
1
Order By: Relevance
“…Adopting linguistic validation algorithms may be helpful, since they do not rely merely on linguistic translation but are rather based on a standardized set of processes to ensure both linguistic appropriateness and invariance of the original meaning, which provides a robust basis for further psychometric evaluations (Acquadro et al, 2004;Epstein et al, 2015). Thus, they are widely used in any scientific field, including human sexuality (Fakhri et al, 2012;Heinemann et al, 2001;Lorca et al, 2021;Malavige et al, 2013;Nowosielski et al, 2021;Peixoto et al, 2020;Pourmomeny et al, 2021;Rušavý et al, 2017). Therefore, due to the need to test the convergent validity of a new Italian measurement scale, a linguistic validation was conducted on the Wilson Sex Fantasy Questionnaire (SFQ; Wilson, 1978Wilson, , 1988, which was selected for the compatibility between the two factorial structures and its wide utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Adopting linguistic validation algorithms may be helpful, since they do not rely merely on linguistic translation but are rather based on a standardized set of processes to ensure both linguistic appropriateness and invariance of the original meaning, which provides a robust basis for further psychometric evaluations (Acquadro et al, 2004;Epstein et al, 2015). Thus, they are widely used in any scientific field, including human sexuality (Fakhri et al, 2012;Heinemann et al, 2001;Lorca et al, 2021;Malavige et al, 2013;Nowosielski et al, 2021;Peixoto et al, 2020;Pourmomeny et al, 2021;Rušavý et al, 2017). Therefore, due to the need to test the convergent validity of a new Italian measurement scale, a linguistic validation was conducted on the Wilson Sex Fantasy Questionnaire (SFQ; Wilson, 1978Wilson, , 1988, which was selected for the compatibility between the two factorial structures and its wide utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the SIS/SES to satisfy criteria for establishing psychometric properties (Velten et al, 2018;Nowosielski et al, 2021;Graham et al, 2006;Bloemendaal & Laan, 2015). Application of the SIS/SES scale has also proven useful; evidence of high SES and SIS scores have been linked to sexual dysfunction and pathology Bancroft et al, 2009;Velten et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The universal nature of psychological mechanisms is often belied by socio-cultural, political, and linguistic manifestations. The SIS/SES has been translated and applied in several countries including Germany, Italy, Portugal and Poland (Velten et al, 2018;Panzeri et al, 2008;Gomes et al, 2018;Nowosielski et al, 2021). While the results are generally supportive, there are some differences in the comprehension of individual items and variation in the optimum factor structure.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the DCM is gaining traction in the international scientific community, with translation and cultural adaptations of the SIS/SES being published in recent years. To date, the scales have been translated in Spanish, 20 German, 21 Portuguese, 12 Italian, 22 Finnish, 23 Polish, 24 and several South Asian languages. 25 For the most part, the three-factor structure has been replicated in these translations.…”
Section: Introductionmentioning
confidence: 99%
“…25 For the most part, the three-factor structure has been replicated in these translations. Yet, several of the published studies have dropped numerous items from the original version, 12,20,23,24 Using a more parsimonious version of the scale, such as the SIS/ SES-SF, could help to replicate its factorial structure across cultures and genders, thus enabling better comparison between studies and helping identify processes contributing to human sexual response.…”
Section: Introductionmentioning
confidence: 99%